Peluang investasi dan daya dukung lingkungan usaha penangkapan ikan di Kabupaten Majene Provinsi Sulawesi Barat - Sutisna, Muhammad Aziz Rizal (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: Majene Regency, which is located in West Sulawesi Province, is part of the Republic of Indonesia State Fisheries Management Area (WPPNRI) 713. It has a coastline length of approximately 125 km2, a sea area of more than 13,124 km2, and a land area of around 947.84 km2. The potential fish resources are 1,026,599 million tonnes per year, mainly consisting of small pelagic fish, large pelagic fish, demersal fish, coral fish, penaeid shrimp, lobsters, crabs, and squid. Methods: This research uses scientific literature sources, government publications, policy documents, academic databases including scientific journals, and books to obtain a comprehensive and up-to-date view. Findings: Data shows that capture fisheries production in Majene Regency produces 7,458 tonnes of marine fisheries products. Conclusion: This increased from the previous year's 4.36 percent from 2017 to 2018. The largest marine fisheries production came from Banggae District, contributing 21.87 percent to Majene Regency's fisheries production. Aquaculture production originating from ponds decreased by 46.36 percent from 2017 to 2018. The amount of investment entering Western Province is still relatively low, namely being ranked 30th out of 34 provinces in Indonesia and in last position. out of 5 provinces in Sulawesi.